Styrsystem för ny pump samt analys av förutsättningar för liknande projekt - Persson, Lukas (My University, 2026)
This project aims to improve the knowledge and understanding within SGS studentbostäder regarding the automation and control systems used in their buildings. The project focused on implementing Modbus communication between a new circulation pump and an existing control system responsible for heating and ventilation in a residential building. The technical work only concerned configuring the software of the control system and an external monitoring program, not the physical installation of any hardware. In enabling Modbus communication between the pump and the rest of the control system the primary goal was to monitor the performance of the pump via the external monitoring program. An investigation was also made to determine if it was possible to control the pump externally using the external monitoring program. The data sent via Modbus from circulation pump to the external monitoring program contained performance data that enabled real-time monitoring of the performance of the pump. Writing to the internal memory of the pump from the external monitoring program was not fully implemented due to a conflict between Modbus and the digital in/outputs used to start and stop the pump. Based on the technical work done, an analysis was done regaring the functionality and limitations of the control system. The analyses also examines the organisational structure of SGS to determine the need and feasibility to work internally with automation and control systems, or if they should continue outsourcing the installation and maintenance of these systems to external parties. The report is written in Swedish.
Keywords: Modbus; control system; circulation pump